It's healthy to travel and enjoy it (Journal of Parents and Teachers, 2014)
The word travel has multiple meanings such as the action of moving from one place to another; the state after administering a hallucinogenic drug; used to name a ticket for public transportation, etc. The following article refers to the first definition and advises on how to do it, what issues to consider, who to travel with, how to travel, etc.
Keywords: travel; travelling; move; tips